Exposure to firearm: impact on psychological health in central India - Saxena, S; Varma, R P; Soman, B (Indian Journal of Community Health, 2013)
Background: The issue of firearm exposure is one of the widespread prevailing problems in today’s world but at the same time it is least talked about. Its psychological effects vary from person to person and the degree of consequences has many variables to measure. The firearm exposure not only implies to an individual but also the whole gambit of social structures around him. Methods: A cross-section study on 505 subjects of the age group 20-45 years from central India was done, where routine social order depends upon massive armament of the citizen. We studied the relationship between socio-demographic variables and firearm exposure with variables of psychological domain of the WHOQOL-BREF. Multivariate logistic regression model was constructed to find the correlates among them. The objectives of the study were to study the attributes of socio demographic variables, which affects psychological health and exposure to firearms in the study population and to see the impact of exposure to firearms on psychological health. Results: Higher education is associated positively with psychological health. The desire to have a gun (OR=1.988, CI 1.306-3.024, p-value <.005) is showing a significant association with low psychological domain score of QOL. Being married (OR=.556, CI .344-.901, p-value <.005) and not Living in a joint family (OR=.581, CI .379-.891, p-value <.005) is associated with poor psychological health. Conclusions: Higher education is the best predictor for good psychological health. Semiskilled workers (farmers and laborers) should be prioritized as high risk groups for adverse life situations. Firearm exposures have a significant impact on psychological health. So, policies directed at rural population should target at specific needs of community.